Phylogenetic, taxonomic and functional diversity of fungal denitrifiers and associated N2O production efficacy. (April 2015) - Mothapo, Nape; Chen, Huaihai; Cubeta, Marc A.; Grossman, Julie M.; Fuller, Fred; Shi, Wei
Abstract: Fungi generally dominate microbial biomass in various soils and play critical roles in ecosystem functioning including nutrient cycling, disease ecology and food production. Therefore, fungal denitrification, phenotypically typified by nitrous oxide (N2 O) production, presents another avenue other than N mineralization and heterotrophic nitrification for progress to better understand the multiple roles of fungi in sustaining the biosphere. The discovery of N2 O production and consequently denitrification in Fusarium oxysporum Schltdl. in early 1970's has led to identification of many taxonomically diverse species of N2 O-producing fungi. This review evaluates the current status of knowledge on species composition of fungal denitrifiers and their N2 O-producing activity. Here we describe challenges with assessment of fungal N2 O-producing activity across genera and suggest prospects for future studies. We also discuss species diversity in order to gain knowledge of important taxonomic and phylogenetic groups mediating N2 O production and provide insight on ecological cues associated with fungal N2 O production. Currently, the extent to which species phylogeny and the functional trait, i.e. N2 O-producing activity, are linked remains to be determined; even so, it is evident that some related taxa exhibit similar N2 O production efficacy than distant relatives. Highlights: N2 O-producing fungi belong mainly to phylum Ascomycota. Sordariomycetes and Eurotiomycetes are major classes of N2 O-producing fungi. Species of Fusarium and teleomorphs are significant to fungal N2 O production. N2 O-producing Fusarium oxysporum is widely distributed across diverse ecosystems. Fungal N2 O-producing activity is 1–5 orders of magnitude lower than bacterial one.